New York klezmer in the early twentieth century : the music of Naftule Brandwein and Dave Tarras - Rubin, Joel, 1955- (Eastman/Rochester studies in ethnomusicology, 2020)
The music of clarinetists Naftule Brandwein and Dave Tarras is iconic of American klezmer music. Their legacy has had an enduring impact on the development of the popular world music genre.